Elispot for Rookies (and Experts Too) - Janetzki, Sylvia (Techniques in Life Science and Biomedicine for the Non-Expert, 2016)
This book provides basic, simple, and logical explanations for choices to be made to run the best Elispot possible. It allows the newcomer to truly understand the best options for specific protocol steps, reagents and materials, and provides even the experienced Elispot user with insight into best practices. The techniques presented here are supported by the author's twenty-plus years of first-hand experience working with this assay, as well as the shared experiences of numerous colleagues and collaborators. .